2019
DOI: 10.3390/s20010080
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring a 28.5 m High Anchored Pile Wall in Gravel Using Various Methods

Abstract: Horizontal displacements of a multiple-anchor pile wall in a 28.5 m deep excavation using the top-down construction method have been monitored using optical fiber (Brillouin optical time-domain reflectometry (BOTDR)), strain gauges, inclinometers, and a topographic survey. This work presents a comparison between these different techniques to measure horizontal displacements in the pile at several stages of the soil excavation process. It was observed that displacements can be separated into two components: Rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The main stream DFOS widely used in strain monitoring based on Brillouin Scattering technology are the BOTDR, BOTDA, and BOFDA [43]. They have been applied to the strain monitoring of various kinds of structures in many industries, such as high anchored pile wall in gravel [44], Bored Pile [45], Pile Foundation [46], Beam Bridges [47], similar material test model [48], steel rails [49], subsea Sensors 2020, 20, 1318 4 of 31 cables [50], geotechnical structures [51], River Levee Collapse, Concrete Structures and yacht [52], tunnel healthy [53], the state of underground copper mine [54], land subsidence [55], airplane structure health [56], and so on.…”
Section: Distributed Fiber Optical Sensor (Dfos) Technologymentioning
confidence: 99%
“…The main stream DFOS widely used in strain monitoring based on Brillouin Scattering technology are the BOTDR, BOTDA, and BOFDA [43]. They have been applied to the strain monitoring of various kinds of structures in many industries, such as high anchored pile wall in gravel [44], Bored Pile [45], Pile Foundation [46], Beam Bridges [47], similar material test model [48], steel rails [49], subsea Sensors 2020, 20, 1318 4 of 31 cables [50], geotechnical structures [51], River Levee Collapse, Concrete Structures and yacht [52], tunnel healthy [53], the state of underground copper mine [54], land subsidence [55], airplane structure health [56], and so on.…”
Section: Distributed Fiber Optical Sensor (Dfos) Technologymentioning
confidence: 99%
“…Figure 10 shows the calculation differences between the ICTool and the DigiPro2 software (ICT-DP2) which has a maximum value of less than 0.005 mm while the maximum value (SM-DP2) between SiteMaster 2012 and DigiPro2 is about 0.10 mm. These deviations are very tiny in comparison with bias and measuring errors (Grodecki et al, 2018;Moffat et al, 2019) or technical requirements (Liu et al, 2011;Pei et al, 2021) of basement diaphragm wall monitoring so they can be omitted.…”
Section: Resultsmentioning
confidence: 99%
“…For example, when processing GK-604D data using Geoslope's DigiPro2 software, without any notes from the manufacturers, an instrument constant of 40000 was selected to obtain the correct displacement value according to the calculation principle of Geokon manufacturer. These confusions in the inclinometer data processing have put the Vietnamese surveyors in an embarrassing situation and there is even a possibility that readings are interpreted incorrectly resulting in misleading wall deflections (Moffat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a reinforced 5 mm optical fiber cable fixed along steel bars was used. Moffat et al [14] showed a comparison between BOTDR, strain gauges, inclinometers, and topographic survey methods to monitor a multiple-anchor pile wall in 28.5 m deep excavation.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, a reinforced 5 mm optical fiber cable fixed along steel bars was used. Moffat et al [14] showed a comparison between BOTDR, strain gauges, inclinometers, and topographic survey methods to monitor a multiple-anchor pile wall in 28.5 m deep excavation. Nowadays, steel-based sheet piles are very often replaced by hybrid composite materials like a polyvinyl chloride matrix locally reinforced with glass fibers [15].…”
Section: Introductionmentioning
confidence: 99%